2021
DOI: 10.31083/j.rcm2202036
|View full text |Cite
|
Sign up to set email alerts
|

Atrioventricular and intraventricular blocks in the setting of acute coronary syndromes: a narrative review

Abstract: Acute coronary syndromes (ACS) might be complicated by atrioventricular (AV) and intraventricular (IV) blocks in a significant number of cases, and often represent a diagnostic and a therapeutic challenge. These conduction disturbances are predictors of adverse prognosis, with complete AV blocks presenting the most severe outcomes, showing an increased in-hospital mortality. With the advent of emergency percutaneous coronary intervention (PCI) and the end of the thrombolysis era, the incidence of both AV and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…So, AV blocks may accompany right coronary artery occlusion [ 31 ]. Also, the results of a narrative study showed that patients with inferior MI and left anterior descending artery obstruction may have a significantly higher risk of developing complete AV node block [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…So, AV blocks may accompany right coronary artery occlusion [ 31 ]. Also, the results of a narrative study showed that patients with inferior MI and left anterior descending artery obstruction may have a significantly higher risk of developing complete AV node block [ 32 ].…”
Section: Discussionmentioning
confidence: 99%